PIK3CA mutation correlates with mTOR pathway expression but not clinical and pathological features in Fibfibroipose vascular anomaly (FAVA) - Yumiko Hori; Katsutoshi Hirose; Michio Ozeki; Kenji Hata; Daisuke Motooka; Shinichiro Tahara; Takahiro Matsui; Masaharu Kohara; Hiroki Higashihara; Yusuke Ono; Kaishu Tanaka; Satoru Toyosawa; et al. (BMC, 2022)
Abstract Background Fibro-adipose vascular anomaly (FAVA) is a rare and new entity of vascular anomaly. Activating mutations in the phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) gene were identified at a frequency of 62.5% in FAVA cases. The PIK3CA mutations excessively activate mammalian target of rapamycin (mTOR) pathway, which promotes angiogenesis and lymphangiogenesis, implying that PIK3CA mutations may act as drivers of FAVAs. This study investigated the correlations between PIK3CA mutational status, clinicopathological features and immunohistochemical expression of the mTOR pathway in a series of FAVA. Methods We retrospectively evaluated the clinical and pathological findings of four FAVA cases. We performed next-generation sequencing (NGS) with a custom panel of genes associated with the mTOR pathway and genes responsible for other vascular anomalies; followed by direct sequencing and immunohistochemical analysis of the mTOR pathway. Results Two PIK3CA-mutation cases and two PIK3CA-wild-type (wt) cases exhibited similar typical clinical features of FAVA. Histological analysis revealed venous malformation, lymphatic malformation, nerves containing enlarged abnormal vessels and fibrofatty tissue were observed regardless of PIK3CA mutational status. In contrast to clinical and histological findings, the immunohistochemical expression of activated AKT and mTOR that are upstream of the mTOR pathway was detected in abnormal vessels of PIK3CA-mutation cases but not in those of PIK3CA-wt cases. However, activated eukaryotic translation initiation factor 4E-binding protein 1 (4EBP1) and ribosomal protein S6 kinase 1 (S6K1), both of which are downstream effectors of the mTOR pathway, were expressed in abnormal vessels of both PIK3CA-mutation and PIK3CA-wt cases. Furthermore, targeting NGS did not find any common genetic mutations involved in the mTOR pathway among PIK3CA-wt cases. Conclusions There was no significant association between the presence of PIK3CA mutations and the clinicopathological features of FAVA, suggesting that the PIK3CA gene is not necessarily involved in the onset of FAVA. FAVAs lacking PIK3CA mutations may be caused by other gene mutations that activate 4EBP1 and S6K1.